SMANTUB (anti tuberculosis smartwatch) integrated with spy-TBC: Early strategy for Tuberculosis eradication based on smartwatch and Aiot-Posbindu-PM-TBC (artificial intelligence of things post for infectious Tuberculosis) - Yuwono, Hasto (Public Health Risk Assesment Journal, 2025)
Background: Progress in efforts to eradicate TB or Indonesia free from TB 2030 should be continued and appreciated in order to move towards a more advanced and visionary future. There is still no special application to overcome TB cases in Indonesia based on AIoT or the internet). The aim of this research is to provide an idea to eradicated TB throught health also social care with advanced technology also innovation. Methods: This article uses a literature review method and presents an innovative approach for eradicating tuberculosis through the PDCA cycle. The focus is on setting goals for progress and creating strategies to reach them. The research proposes a new innovation, Smantub, combined with technology to decrease TB cases. Findings: The "Smantub" smartwatch, integrated with Spy-TBC technology and powered by AIoT, is a cutting-edge tool for early prevention and management of tuberculosis (TB) in Indonesia. By utilizing Big Data, WebApp, and location tracking, as well as AIoT-Posbindu-PM-TBC, it can play a crucial role in reducing TB prevalence, which remains high in the country. The Smantub smartwatch aims to address health threats, prevent deaths, and control the spread of TB. With this innovative technology, Indonesia can work toward becoming TB-free by 2030, supported by the efforts of Jejamoe Café. Conclusion: Smartwatch “Smantub” can be used as a cutting-edge tool or technology in early and mature prevention efforts to reduce the prevalence of TB which is currently still high in Indonesia. Novelty/Originality of this article: Smantub helps overcome the problem of TB, especially in controlling the location of sufferers and controlling the prevention of transmission.